Six days in August : the story of Stockholm syndrome - King, David, 1970- (W.W. Norton & Company, 2020)
"The definitive account of the bizarre hostage drama that gave rise to the term "Stockholm Syndrome." On the morning of August 23, 1973, a man wearing a wig, makeup, and a pair of sunglasses walked into the main branch of Sveriges Kreditbank, a prominent bank in central Stockholm. He ripped out a submachine gun, fired it into the ceiling, and shouted, "The party starts!" This was the beginning of a six-day hostage crisis-and media circus-that would mesmerize the country, drawing into its grip everyone from Sweden's most notorious outlaw to the prime minister. By the end, the police and press alike would have a new way to understand the complicated emotional relationship between captor and captive. Based on a wealth of previously unavailable sources, including rare film footage, and unprecedented access to the main participants, Six Days in August is a groundbreaking work of nonfiction-a rich human drama of loyalty and betrayal, obedience and defiance, fear and attraction"--